The Rate of S-Element Transformation to Sulfate on Three Kinds of Soils With and Without Addition of Organic Matter - H Muhammad; S Sabiham; A Rachim; H Adijuwana (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2005)
Defiency of sulfur were found at many areas of farming in Indonesia. The aim of this experiment was to Icnow the rate ofS-element tranformation to sulfate on three kinds of soil without and added of organic matter. The experiment was conducted using a Randomized Complete Design with factorial pattern consist of two factors and two replications. The first factor is kinds of soil, i.e. Udic Haplusters, Typic Haplustepts, and Oxyaquic Udipsamment. The second factor is dosage of S-element consist offive levels i.e. 20, 40, 60, 80, and 100 mg kg